2019
DOI: 10.1021/acsapm.9b00832
|View full text |Cite
|
Sign up to set email alerts
|

Green Toughness Modifier from Downstream Corn Oil in Improving Poly(lactic acid) Performance

Abstract: A green multifunctional toughness modifier for poly(lactic acid) (PLA) was successfully synthesized from the derivatives of downstream corn oil (a coproduct of bioethanol industry) and itaconic acid. The efficiency of the synthesized toughness modifier, monomethyl itaconated epoxidized downstream corn oil (MIECO), was evaluated with a different loading percentage of it (5−15 wt %) in the PLA matrix. A dynamic cross-linking strategy was taken to achieve toughened PLA by using multifunctional MIECO in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…This lower increase in elongation values was due to the lower content of epoxy groups in palm oil (3.23%) with respect to chia oil (6.71%), which is one of the main parameters to be taken into account. For example, other authors have reported similar increases of 700% or even higher using epoxidized vegetable oils with content of epoxy groups around 5.8% [ 36 , 40 , 41 ]. Thus, stronger interactions occurred as epoxy content increased due to the increased presence of reactive groups Therefore, in view of the results obtained, it seems that once epoxy group values of 5.8% or higher were reached, a saturation effect was shown, not reaching further increases in the elongation at break.…”
Section: Resultsmentioning
confidence: 87%
“…This lower increase in elongation values was due to the lower content of epoxy groups in palm oil (3.23%) with respect to chia oil (6.71%), which is one of the main parameters to be taken into account. For example, other authors have reported similar increases of 700% or even higher using epoxidized vegetable oils with content of epoxy groups around 5.8% [ 36 , 40 , 41 ]. Thus, stronger interactions occurred as epoxy content increased due to the increased presence of reactive groups Therefore, in view of the results obtained, it seems that once epoxy group values of 5.8% or higher were reached, a saturation effect was shown, not reaching further increases in the elongation at break.…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, reactive extrusion has been shown to be an effective and economic method to improve the compatibility of polymer blends such as PLA/PBS, PBS/poly­(butylene adipate- co -terephthalate) (PBAT), PHB/PBS, etc. via in situ polymer chain modifications in the extruder. , Except for the dicumyl peroxide (DCP), which emits a strong pungent odor, it was found that the other organic peroxide such as Luperox cannot improve the compatibility and mechanical toughness of PHBV/PCL blends especially at high PHBV contents. A PHBV/PCL/peroxide reactive extrusion study was conducted by Cavallaro et al, and it was found that the tensile stress at break was lower for the reacted blends with peroxide due to insufficient interfacial strength between the two polymers .…”
Section: Introductionmentioning
confidence: 99%
“…Wang等 [29] 图 5 衣康酸甲酯(a)及其改性环氧化玉米油(b)的合成路线 图 [33] (网络版彩图) 图 6 CNCaq-rD和CNCaq-rD-PDLA两种增韧改性剂的合成 路线 [36] (网络版彩图) Figure 6 Synthetic routes of CNCaq-rD and CNCaq-rD-PDLA two toughening modifiers [36] [37] (网络版彩图) 图 8 酯化淀粉颗粒(a)和核壳结构淀粉纳米粒子(b)的制备示意图 [40] (网络版彩图)…”
Section: 和断裂伸长率逐渐下降unclassified
“…Synthesis route of itaconic acid methyl ester (a) and its modified epoxidized corn oil (b)[33] (color online).…”
mentioning
confidence: 99%